Nitrogen addition to soil affects microbial carbon use efficiency: Meta‐analysis of similarities and differences in 13C and 18O approaches. (26th May 2022) - Hu, Junxi; Huang, Congde; Zhou, Shixing; Kuzyakov, Yakov
Abstract: The carbon use efficiency (CUE) of soil microorganisms is a critical parameter for the first step of organic carbon (C) transformation by and incorporation into microbial biomass and shapes C cycling in terrestrial ecosystems. As C and nitrogen (N) cycles interact closely and N availability affects microbial metabolism, N addition to soil may shift the microbial CUE. We conducted a meta‐analysis (100 data pairs) to generalize information about the microbial CUE response to N addition in soil based on the two most common CUE estimation approaches: (i) 13 C‐labelled substrate addition ( 13 C‐substrate) and (ii) 18 O‐labelled water addition ( 18 O‐H2 O). The mean microbial CUE in soils across all biomes and approaches was 0.37. The effects of N addition on CUE, however, were depended on the approach: CUE decreased by 12% if measured by the 13 C‐substrate approach, while CUE increased by 11% if measured by the 18 O‐H2 O approach. These differences in the microbial CUE response depending on the estimation approach are explained by the divergent reactions of microbial growth to N addition: N addition decreases the 13 C incorporation into microbial biomass (this parameter is in the numerator by CUE calculation based on the 13 C‐substrate approach). In contrast, N addition slightly increases (although statistically insignificant) the microbial growth rate (in the numerator of the CUE calculation when assessed by the 18 O‐H2 O approach), significantly raising the CUE. We explained these N addition effects based on CUE regulation mechanisms at the metabolic, cell, community, and ecosystem levels. Consequently, the differences in the microbial responses (microbial growth, respiration, C incorporation, community composition, and dormant or active states) between the 13 C‐substrate and 18 O‐H2 O approaches need to be considered. Thus, these two CUE estimation approaches should be compared to understand microbially mediated C and nutrient dynamics under increasing anthropogenic N input and other global change effects. Abstract : Microbial carbon use efficiency (CUE) is a crucial for the first step of organic C transformation in soil. Our meta‐analysis elucidates the microbial mechanisms of CUE response to anthropogenic N input: microbial growth, respiration and C incorporation. These mechanisms are discussed and specific aspects of short‐term C and energy transformation in soil are evaluated on metabolic, cellular, community, and ecosystem scales.